Trade liberalization, democratization and technology adoption - Matteo Cervellati; Alireza Naghavi; Farid Toubal (Institute for the Study of Labor (IZA), 2013)
We study the role of trade liberalization, democratization and their interaction for technology adoption. A general equilibrium theory with heterogeneous skills predicts a complementarity between trade and political regimes. Openness should accelerate technology adoption if coupled with democratization but may lead to a slow down if these regime changes are imbalanced. We use panel data on technology adoption at the sectoral level for the period 1980-2000 by exploiting within country variation and the heterogenous timing of openness and democratization. The results document the existence of robust positive interactions between these institutional changes for technology adoption and productivity growth.
Keywords: F16; J24; O14; P51; F59; 330; trade openness; democratization; political economy theory; technology adoption; sector level panel data; cross-country analysis; Innovationsdiffusion; Außenhandelsliberalisierung; Politik der offenen Tür; Demokratisierung; Branche; Public Choice; Schätzung; Welt